Mechanical And Corrosion BEHAVIOR OF In-SITU PARTICULATES (Al2O3, Tib2, Tic) Reinforced Fe-Al Intermetallic Composites - Huy, Tran Duc (2010)
The purpose of this study is to synthesize iron aluminide intermetallic composite with in situ particulates (Al2O3, TiB2, TiC). Powder metallurgy method was used in this work to produce iron aluminide solid solution as matrix by mechanical alloying. It was found that mechanical alloying process plays a significant role in solid solution formation and later on the mechanical properties. The optimum conditions to produce iron aluminide composite in this particular work are: (1) milling time is 10 h at speed of 300 rpm, (2) consolidation by hydraulic press at 350 MPa and (3) sintering at 1300 oC for 1 h. Matrix of iron aluminide can form Fe3Al or FeAl depending on the Al concentration.